Roots of the Black Chicago Renaissance : New Negro Writers, Artists, and Intellectuals, 1893-1930 - Hine, Darlene Clark; Reed, Christopher Robert; Courage, Richard A., 1946- (Book collections on Project MUSE., 2020)
"The Black Chicago Renaissance emerged from a foundational stage that stretched from the 1893 World's Columbian Exposition to the start of the Great Depression. During this time, African American innovators working across the landscape of the arts set the stage for an intellectual flowering that redefined black cultural life. Richard A. Courage and Christopher Robert Reed have brought together essays that explore the intersections in the backgrounds, education, professional affiliations, and public lives and achievements of black writers, journalists, visual artists, dance instructors, and other creators working in the late nineteenth and early twentieth centuries. 00Organized chronologically, the chapters unearth transformative forces that supported the emergence of individuals and social networks dedicated to work in arts and letters. The result is an illuminating scholarly collaboration that remaps African American intellectual and cultural geography and reframes the concept of urban black renaissance"--Publisher's description